Manajemen Pendidikan Karakter untuk Meningkatkan Nilai Religius Santri Melalui Kajian Kitab Akhlak Lil Banin di Pondok Pesantren Bait Et-Tauhied Kota Serang - Diah Robiatul Adawiah; Agus Gunawan; Nana Suryapermana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Character education is an important component and has a great influence on the success of religious activities. The purpose of this study is to describe the management of student character education in increasing religious values through the study of the book of morals lil banin. This study uses a qualitative descriptive method. In the data collection technique, the researcher uses observation, interview and documentation techniques. The data analysis technique uses data reduction, data presentation and conclusion drawn, as well as validity test using data triangulation techniques. Based on the results of the study, it shows that; 1) Character education planning includes planning vision and mission, preparation of work programs, the formation of a schedule for the implementation of each activity, as well as the division of structure and job description; 2) The implementation of character education at the Bait Et-Tauhied Islamic Boarding School has carried out various religious character formation programs. This is evidenced through several coaches carried out, namely examples, training, taking lessons, giving advice, and providing rewards and punishments; 3) Supervision of character education at the Bait Et-Tauhied Islamic Boarding School, including supervising students, guiding students in the implementation of activities, conducting evaluation meetings; 4) The values of religious character through the study of the book of Morality Lil Banin which are instilled in the Bait Et-Tauhied Islamic Boarding School are as follows: (a) Morality to Allah, (b) Respect for both parents, (c) Respect for teachers and friends, (d) Patience in learning and discussion, and (e) Honesty.